Teaching Two-Way Frequency Tables Through Misconceptions (pp. 43–49) - Jakes, Lindsey (Ohio Journal of School Mathematics, 2019)
During my first year of teaching, I thought I was alone in suffering through awkward moments as I made content mistakes in front of my students. The more I experienced these instances, the more I was able to strengthen my understanding of content and pedagogy. Why not provide my students with similar experiences to deepen their understanding of mathematics? In this article, I discuss how I used a misconception I had about two-way frequency tables to help students achieve a better understanding of how the variables in two-way frequency tables are dependent on each other.